LEVELS OF UNDERSTANDING OF THE ARTWORK AND THEIR POSSIBLE CONTRADICTORY CLASH - emotional-artistic, complex, contradictory process, clarification, perception, imagination, right combination, personality.; Z.O.Karimova (Journal of new century innovations, 2022)
This article discusses the difficulties of understanding a literary text, since the understanding of a literary text moves from verbal to substantive, the combination of which gives a logical understanding; from it, the movement is directed to understanding motives, goals, and subtext. In this direction, approximately, the process of perception of the actual and emotional-artistic content of the work takes place.